Pengaruh Penggunaan Media Pembelajaran Wordwall Terhadap Hasil Belajar IPAS Kelas IV SDN 10 Langkai - Dimas Fathur Rahman; Roso Sugiyanto; Ichyatul Afrom (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Learning media has an important role in supporting the achievement of maximum learning objectives. When viewed from the way students learn, we know that in one class students have different ways of learning, some learn quickly using audio, visual, and some see the form concretely. then this study aims to determine the effect of using wordwall learning media on student learning outcomes in IPAS class IV SD Negeri 10 Langkai Kota Palangka Raya. The method used in this research is experimental research method. The design used in this research is One-group Pretest-Posttest Design. Sampling in this study used saturated sampling technique (total sample) because the researcher used all members of the population as samples with a total of 17 respondents. Pre-Test and Post-Test are used to determine student learning outcomes in the form of questions with a form of content. Based on the results of the Paired Sample T-Test test, the sig.2-tailed result is 0.001, this value is greater than 0.05, so Ha is accepted and Ho is rejected. Meanwhile, when compared to the tcount value with the ttable, there is a tcount value of 16,000> 1,746 from the ttable value, so Ha is accepted and Ho is rejected. So it is concluded that there is a positive effect of the use of wordwall learning media on student learning outcomes in IPAS subjects on the material of natural appearances and their utilization in class IV SD Negeri 10 Langkai Kota Palangka Raya.